2020
DOI: 10.1155/2020/2198308
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of miR-103 in Patients with Sepsis and Noninfectious SIRS and Its Regulatory Role in LPS-Induced Inflammatory Response by Targeting TLR4

Abstract: Background. Sepsis is a life-threatening condition and a systemic inflammatory response syndrome (SIRS) driven by infection. This study aimed at investigating the expression of microRNA-103 (miR-103) in sepsis patients, evaluating its diagnostic value, and exploring the regulatory effect of miR-103 on LPS-induced inflammation in monocytes. Methods. Expression of miR-103 was measured using quantitative real-time PCR. A receiver operating characteristics curve was plotted to evaluate the diagnostic vale of miR-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
(31 reference statements)
1
5
0
1
Order By: Relevance
“…miRNAs have been considered as ideal diagnostic tools for various human diseases due to their abnormal expression and stability in blood samples ( 27 ). For example, decreased levels of serum miR-103 may be used as non-invasive diagnostic biomarkers in patients with sepsis ( 28 ) and decreased levels of serum miR-375 may serve as biomarkers for the diagnosis of osteosarcoma ( 29 ). Considering the increased expression of miR-1323 in patients with GDM, ROC curves were plotted based on the miR-1323 expression and revealed that miR-1323 may be a potential diagnostic biomarker for patients with GDM.…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs have been considered as ideal diagnostic tools for various human diseases due to their abnormal expression and stability in blood samples ( 27 ). For example, decreased levels of serum miR-103 may be used as non-invasive diagnostic biomarkers in patients with sepsis ( 28 ) and decreased levels of serum miR-375 may serve as biomarkers for the diagnosis of osteosarcoma ( 29 ). Considering the increased expression of miR-1323 in patients with GDM, ROC curves were plotted based on the miR-1323 expression and revealed that miR-1323 may be a potential diagnostic biomarker for patients with GDM.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies in sepsis have demonstrated similar findings with lower levels of microRNAs (miR-23a-5p, miR-26a-5p, miR-26b-5p, miR-103a-3p, miR-150-5p) in septic patients compared with healthy controls; however, systemic levels of these cellular microRNAs were increased in patients with severe sepsis or sepsis mortality. 16,20,37,41,42 Given the concurrent findings between PtPs in our study and sepsis studies, these microRNAs may yield early predictive value for trauma patients at risk for infectious complications and poor outcomes in trauma. Further evaluation of miR-103a-3p as a marker of VTE is merited given that the association between elevated levels of miR-103a-3p and VTE has been previously described in patients with recurrent VTE and potential mechanisms of action have been proposed.…”
Section: Discussionmentioning
confidence: 63%
“…The Wagner classification of the DFUs selected in this study was class II‐III, with mild to moderate infection status. Previous research has found that serum miR‐103 expression is reduced in patients with non‐infectious systemic inflammatory response syndrome and sepsis compared with healthy controls 40 . However, some studies have shown that the expression level of miR‐103 is increased in the peripheral blood of patients with type 2 diabetes 36,37 .…”
Section: Discussionmentioning
confidence: 97%
“…Previous research has found that serum miR‐103 expression is reduced in patients with non‐infectious systemic inflammatory response syndrome and sepsis compared with healthy controls. 40 However, some studies have shown that the expression level of miR‐103 is increased in the peripheral blood of patients with type 2 diabetes. 36 , 37 These results suggest that hyperglycemia and inflammatory responses may mutually inversely regulate the expression of miR‐103 in peripheral blood.…”
Section: Discussionmentioning
confidence: 99%